RELATIONSHIP BETWEEN AGE AND PARITY OF PREGNANT WOMEN ANEMIA INCIDENCES IN MAYANGREJO - Annisa Emma Aznam; Lilik Inayati (Universitas Airlangga, 2021)
Maternal mortality cases in Indonesia are still high. The Population Survey Census Rates or Survey Penduduk Angka Sensus (SUPAS) data in 2015 found a total of 305 maternal deaths per 100,000 births. Maternal mortality cases can be caused by complications of pregnancy. The age of the pregnant women are linked to their risk for complications during pregnancy. Parity can also affect pregnant women's health conditions. Health problems that can be faced by pregnant women of a risky age and parity are bleeding, which can cause pregnant women to experience anemia. Several studies have found a significant relationship between age and parity with the incidence of anemia in pregnant women. Therefore, it is important to test the relationship between age and parity on the incidence of anemia in pregnant women in Mayangrejo, Bojonegoro. The purpose of this study was to find the relationship between age and parity in the incidences of anemia in pregnant women. The result showed that there is no relationship between age and parity in the incidences of anemia in pregnant women in Mayangrejo, Bojonegoro. This result may be due to the fulfillment of nutritional needs and good knowledge about the risks of pregnancy.